MCAT organic chemistry review notes - Kaplan, Inc. (New York, NY : Kaplan Pub., 2010)
"Comprehensive review, practice, and strategies"--Cover.
Includes index.
Issued in container: MCAT complete 5-book subject review.
Volume copyrighted 2015 misnumbered as: 2nd edition (i.e., earlier 2012 volume numbered 3rd edition).
Keywords: Medical College Admission Test -- Study guides -- Periodicals; Medical colleges -- United States -- Entrance examinations -- Study guides -- Periodicals; Chemistry, Organic -- Examinations -- Study guides -- Periodicals; STUDY AIDS -- MCAT (Medical College Admission Test); STUDY AIDS -- Study Guides; STUDY AIDS -- Tests; Chemistry, Organic -- Examinations; Medical College Admission Test; Medical colleges -- Entrance examinations; United States; Examinations; Periodicals; Study guides; Examinations; Study guides